2021
DOI: 10.1001/jamaoncol.2021.1700
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Performance of Transvaginal Ultrasonography for Evaluation of Postmenopausal Bleeding in a Simulated Cohort of Black and White Women in the US

Abstract: IMPORTANCEBlack women in the US with endometrial cancer (EC) are more likely to be diagnosed with advanced-stage disease independent of insured status and histologic type. The most common way of diagnosing EC at early stages is through screening of people with postmenopausal bleeding to detect endometrial thickness (ET). This approach may disproportionately underperform in Black women secondary to a higher prevalence of fibroids and nonendometrioid EC in this population, both of which affect the quality of ET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Women who might benefit most from the WID-qEC in the near future might be (1) women presenting with abnormal bleeding or other symptoms suggestive of ECs undergoing triage for malignancies, in particular those for whom currently available tests (eg, ultrasound) are less reliable. 8 For example, although the number of non-White women in our settings was low, the performance of the WID-qEC to detect EC was similar in White and non-White women; and (2) women at high risk of developing EC. The WID-qEC exhibited a high NPV in all settings.…”
Section: Discussionmentioning
confidence: 74%
“…Women who might benefit most from the WID-qEC in the near future might be (1) women presenting with abnormal bleeding or other symptoms suggestive of ECs undergoing triage for malignancies, in particular those for whom currently available tests (eg, ultrasound) are less reliable. 8 For example, although the number of non-White women in our settings was low, the performance of the WID-qEC to detect EC was similar in White and non-White women; and (2) women at high risk of developing EC. The WID-qEC exhibited a high NPV in all settings.…”
Section: Discussionmentioning
confidence: 74%
“…These studies suggest that the incorporation of serum HE4 into algorithms that include factors, such as endometrial thickening, age, menopausal status and BMI, could improve the accuracy of serum HE4 for distinguishing EC from benign endometrial conditions, with REM and REM-B showing the most promising results. A recent study showed that the optimum cut-off for endometrial thickness on TVUS may vary according to race, which may need to be considered in algorithms that include TVUS [ 120 ].…”
Section: He4 In Combination With Other Markersmentioning
confidence: 99%
“…A simulated retrospective cohort study, from the Surveillance, Epidemiology and End Results (SEER) data, demonstrated a sensitivity of 47.5% (95% CI 46.0 to 49%) using a cut off of ≥4 mm in black women, compared to a sensitivity of 87.9% (95% CI 87.6 to 88.3%) in white women. [85] Poorer diagnostic test performance of TVS in black women was consistent when using a ≥3 mm or ≥5 mm cut off.…”
Section: Recommendationsmentioning
confidence: 86%